Cytokinin-Specific Glycosyltransferases Possess Different Roles in Cytokinin Homeostasis Maintenance - Šmehilová, Mária; Dobrůšková, Jana; Novák, Ondřej; Takáč, Tomáš; Galuszka, Petr (Frontiers in Plant Science, 2016)
Plant hormones cytokinins (CKs) are one of the major mediators of physiological responses throughout plant life span. Therefore, a proper homeostasis is maintained by regulation of their active levels. Besides degradation, CKs are deactivated by uridine diphosphate glycosyltransferases (UGTs). Physiologically, CKs active levels decline in senescing organs, providing a signal to nutrients that a shift to reproductive tissues has begun. In this work, we show CK glucosides distribution in Arabidopsis leaves during major developmental transition phases. Besides continuous accumulation of N-glucosides we detected sharp maximum of the glucosides in senescence. This is caused prevalently by N7-glucosides followed by N9-glucosides and specifically also by trans-zeatin-O-glucoside (tZOG). Interestingly, we observed a similar trend in response to exogenously applied CK. In Arabidopsis, only three UGTs deactivate CKs in vivo: UGT76C1, UGT76C2 and UGT85A1. We thereby show that UGT85A1 is specifically expressed in senescent leaves whereas UGT76C2 is activated rapidly in response to exogenously applied CK. To shed more light on the UGTs physiological roles, we performed a comparative study on UGTs loss-of-function mutants, characterizing a true ugt85a1-A loss-of-function mutant for the first time. Although no altered phenotype was detected under standard condition we observed reduced chlorophyll degradation with increased anthocyanin accumulation in our experiment on detached leaves accompanied by senescence and stress related genes modulated expression. Among the mutants, ugt76c2 possessed extremely diminished CK N-glucosides levels whereas ugt76c1 showed some specificity towards cis-zeatin (cZ). Besides tZOG, a broader range of CK glucosides was decreased in ugt85a1-A. Performing CK metabolism gene expression profiling, we revealed that activation of CK degradation pathway serve as a general regulatory mechanism of disturbed CK homeostasis followed by decreased CK signaling in all UGT mutants. In contrast, a specific regulation of CKX7, CKX1 and CKX2 was observed for each individual UGT mutant isoform after exogenous CK uptake. Employing an in silico prediction we proposed cytosolic localization of UGT76C1 and UGT76C2, that we further confirmed by GFP tagging of UGT76C2. Integrating all the results, we therefore hypothesize that UGTs possess different physiological roles in Arabidopsis and serve as a fine-tuning mechanism of active CK levels in cytosol.